PENGEMBANGAN MEDIA POP-UP BOOK MATERI KOSAKATA BAHASA INDONESIA SISWA KELAS II SDN NGADI MOJO TAHUN AJARAN 2023/2024 - Ulantika, Ayu; Rian Damariswara; Endang Sri Mujiwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by teachers who predominantly used the lecture method and did not use supporting tools such as learning media. The aim of this research is to determine the validity, practicality and effectiveness of the Pop-Up Book media for Indonesian vocabulary material for class II students at SDN Ngadi Mojo. This research uses research and development methods with the ADDIE development model. The development model used to develop Pop-Up Book media refers to the ADDIE development model, which includes 5 stages, namely 1) Analysis Stage, 2) Design Stage, 3) Development Stage, 4) Implementation Stage, and 5) Evaluation Stage. The subjects in this research were teachers and students of class II SDN Ngadi Mojo Kediri. The data collection techniques were questionnaires and tests, while the data analysis technique used was the Likert scale. The results of this research produced Pop-Up Book media with Indonesian vocabulary material which was declared very valid after validation by media experts and material experts with a percentage of 88%. From the results of the questionnaire, teacher and student responses obtained a percentage of 85.8%, including the very good category. Meanwhile, student learning outcomes obtained a percentage of 85.65% and were declared very effective.